1988
DOI: 10.1128/iai.56.1.64-70.1988
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus sanguis surface antigens and their interactions with saliva

Abstract: Saliva-binding molecules of Streptococcus sanguis and their receptors were investigated. Streptococcal cell surfaces were extracted with a barbital buffer and examined immunochemically. Strains G9B and Blackburn, which adhere specifically to saliva-coated hydroxyapatite via immunologically related adhesins, possess 80-, 62-, and 52-kilodalton (kDa), and 52-, 42-, and 29-kDa polypeptides, respectively, which correlate with adhesion to saliva-coated hydroxyapatite. Nonadherent strains Adhand M-5 lack these antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Negative controls included blocking buffer alone to control for any non-specific binding of P. gingivalis to the nitrocellulose; and S. gordonii OB219 that lacks the Ssp adhesins and does not support P. gingivalis biofilm development (Demuth et al, 1996;Lamont et al, 2002). In addition, for each mutant showing a biofilm defective phenotype, a membrane with deposited S. gordonii cells was probed with anti-S. gordonii whole cell polyclonal antibodies (1:3000) (Lamont et al, 1988) and biotinylated secondary antibody to ensure equivalent numbers of S. gordonii were present on the nitrocellulose. To corroborate the fidelity of biotin labelled cells as a measure of P. gingivalis numbers, P. gingivalis cells were labelled with [ 3 H]-thymidine and numbers determined by scintillation counting of excised spots of the nitrocellulose (Lamont and Rosan, 1990).…”
Section: General Molecular Techniquesmentioning
confidence: 99%
“…Negative controls included blocking buffer alone to control for any non-specific binding of P. gingivalis to the nitrocellulose; and S. gordonii OB219 that lacks the Ssp adhesins and does not support P. gingivalis biofilm development (Demuth et al, 1996;Lamont et al, 2002). In addition, for each mutant showing a biofilm defective phenotype, a membrane with deposited S. gordonii cells was probed with anti-S. gordonii whole cell polyclonal antibodies (1:3000) (Lamont et al, 1988) and biotinylated secondary antibody to ensure equivalent numbers of S. gordonii were present on the nitrocellulose. To corroborate the fidelity of biotin labelled cells as a measure of P. gingivalis numbers, P. gingivalis cells were labelled with [ 3 H]-thymidine and numbers determined by scintillation counting of excised spots of the nitrocellulose (Lamont and Rosan, 1990).…”
Section: General Molecular Techniquesmentioning
confidence: 99%
“…The colutnn was washed with Tris buffer and eluted with a linear gradient of 0 to 0.3 M NaCl. Fractions were monitored spectrophototnetrically at 215 ntn and by sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGF) (13,16) with the Bio-Rad silver stain (Bio-Rad Laboratories, Richtnond, CA). Satnples containing fimbriae were pooled, dialyzed overnight against 4 liters of 0.03 M Tris-HCl pH 8.0 and concentrated in an Atnicon model 52 filtration unit (Atnicon, Beverly, MA).…”
Section: Isoiation Of P Gingivalis Fimbriaementioning
confidence: 99%
“…In contrast, neither the adhesion of the mutant nor the amount of A antigen detected in Adh was affected by growth rate. The A antigen contained polypeptides of 80, 62, and 52 kDa which we previously found to be associated with the adhesion of G9B to SHA (24). The evidence suggests the A antigen is the native form of the antigen complex responsible for the adhesion of S. sanguis G9B to salivary pellicle.…”
mentioning
confidence: 67%
“…All of the studies reported here used the same pools of antisera and the IgG derived from these pools. Mouse anti-80-kDa serum was prepared using essentially the same protocol described previously for rabbit anti-80-kDa serum (24,25), In brief barbital extracts of G9B were subjected to SDS-PAGE (see below) and the 80-kDa band was eut out of the gel, macerated in 0.15 NaCI and mixed with an equal volume (ca. 0.2 ml) of Freund's complete adjuvant.…”
Section: Methodsmentioning
confidence: 99%